Combating economic crime through financial surveillance: An analysis of financial surveillance as a tool of prevention - Bennmarker,Esther (2026)
Can institutional expansion be interpreted as a form of state control or surveillance?Globalization and the digital era have enabled criminals to commit financial crimes and financing terrorism by moving money across borders, making it more difficult for national authorities to detect and prevent such crimes. In response to raised financial crimes, institutions have expanded their mandate and implemented cooperation across the private and public sector, partly by exchange of big data sets of personal information. The development raises important questions regarding privacy, secrecy, and whether personal information is handled responsibly. This thesis examines these issues through the analytical framework ‘What’s the Problem Represented to Be? (WPR)’, applying a systematic analytic policy critical method. Policy documents from the European Union and Sweden are analyzed and compared, aiming at comparing the supranational and national level. The findings are further discussed through a theoretical framework developed for this thesis, building on the theorization of the surveillant assemblage, surveillance capitalism and ethical and democratic outcomes. The study concludes that institutional expansion aiming at combating financial crime can be understood as a form of surveillance and state control, and further as a democratic paradox. The discussion highlights technical vulnerabilities connected to Artificial Intelligence and the digital era, as well as the implications of surveillance for innocent individuals. It also explores whether a line can be drawn between different democratic concerns related to security, privacy, and governance. Finally, suggestions for further research are presented, emphasizing the importance of remaining aware of potential risks in an increasingly digitalized society.
Keywords: Financial surveillance; institutional expansions; European Union and Sweden; state control; democracy; surveillance governance; financial crime; financial intelligence units